"TRASH" Transolecranon Fracture-Dislocation with Occult Osteochondral Coronoid Fracture: A Case Report. Issue 2 (6th April 2022) - Zheng, Jenny L.; Shah, Apurva S.; Nguyen, Jie; Baldwin, Keith D.
Abstract : Case: A 7-year-old girl sustained a radiographic appearance seemed harmless (TRASH) elbow lesion after falling from play equipment. Initial radiographs demonstrated a transolecranon fracture-dislocation. Additional injury was suspected, given valgus instability after reduction. Subsequent magnetic resonance imaging (MRI) revealed a large osteochondral coronoid fragment only partially visible on initial radiographs and computed tomography (CT). Successful outcomes were achieved by ulnar nerve decompression, open reduction, and fixation. Conclusion: TRASH lesions, including this osteochondral coronoid injury, may be overlooked in younger children because of an abundance of unossified cartilage. A high index of suspicion and early MRI can lead to successful diagnosis and treatment.